Circulating tumour cell PD-L1 test for head and neck cancers. (December 2017) - Kulasinghe, Arutha; Kenny, Liz; Punyadeera, Chamindie
Highlights: Immunotherapy in head and neck cancer has shown durable responses. The correct patient needs to be given the correct treatment. Tumour PD-L1 positivity ranges significantly. Circulating tumour cells may provide an avenue to non-invasively determine patients likely to benefit from immunotherapy. Abstract: Immune checkpoint inhibitors have gained traction over the last few years in the treatment of metastatic/recurrent head and neck squamous cell carcinoma (HNSCC) patients. Monoclonal antibodies that block the programmed death 1 (PD-1) receptor and its major ligand, PD-L1, have shown durable responses and low toxicity profiles. There are currently no validated predictive biomarkers to select patients likely to respond to anti-PD-1/PD-L1 therapy to avoid unwanted side effects and to reduce healthcare expenditure. A circulating tumour cell (CTC) PD-L1 assay could be developed as a companion diagnostic tool to potentially predict the efficacy of immune checkpoint blockade treatments.